Epidemiology of hepatitis B and C virus infections among patients who booked for surgical procedures at Felegehiwot referral hospital, Northwest Ethiopia - Asemahagn, Mulusew Andualem (PLoS One, 2020)
BACKGROUND: Hepatitis B virus(HBV) and hepatitis C virus(HCV) are the main causes of cirrhosis, liver cancer, and death. This study aimed to determine the seroprevalence and associated factors of HBV surface antigen(HBsAg) and anti-HCV among patients screened for surgery at Felegehiwot referral hospital, Northwest Ethiopia. METHODS: A hospital-based cross-sectional study was conducted among 433 patients in 2018. Data on socio-demographic and risk factors were collected by an exit interview using a pretested structured questionnaire. A venous blood sample of 5ml was collected from each participant, and serum was tested for HBsAg and anti-HCV using one-step rapid test kits and enzyme-linked immunosorbent assay. Multivariable logistic regression analysis was computed to identify factors associated with HBV and HCV infections. The odds ratio with 95%CI was used to describe the strength of association and statistical significance. RESULTS: A total of 422 patients gave data and included in the analysis. The mean age of patients was 36±5 years. About two-thirds, 269(64%) and 274(65%) patients were males, and from rural areas, respectively. The seroprevalence of HBsAg was 34(8%) followed by 18(4.3%) anti-HCV and 4(0.9%) co-infections. Being single(AOR = 1.96, 95%CI = 1.12–3.10), rural residence (AOR = 2.68, 95%CI = 1.28–5.61), ever heard about HBV (AOR = 2.41, 95%CI = 1.18–5.20), having multiple sexual partners(AOR = 2.85, 95%CI = 1.30–5.58), HIV positive(AOR = 3.14, 95%CI = 1.31–7.61), history of tooth extraction(AOR = 3.0, 95%CI = 1.40–6.56), hospitalization history(AOR = 2.95, 95%CI = 1.26–5.81), sharing of sharp instruments (AOR = 3.86, 95%CI = 1.82–8.79), and had blood contact(AOR = 2.64, 95%CI = 1.14–5.42) were statistically significant factors to HBV infection. Similarly, sharing of sharp instruments(AOR = 4.65, 95%CI = 1.32–15.1), tooth extraction practice(AOR = 2.81, 95%CI = 1.12–6.56), surgical history (AOR = 3.68, 95%CI = 1.64–9.82), hospitalization history(AOR = 4.51, 95%CI = 1.62–8.35) and had blood contact(AOR = 3.2, 95%CI = 1.56–8.51) were significant factors to HCV infection. CONCLUSION: The seroprevalence of HBsAg and ant-HCV was high compared to WHO and previous study findings. Giving special attention to awareness creation, rural settings, improving personal behaviors, infection prevention activities of health facilities, quality of healthcare procedures is crucial to prevent viral hepatitis infection.